The guide to managing postproduction for film, TV, and digital distribution - Spohr, Susan J.
"The updated third edition of this popular book offers a clear and detailed overview of the postproduction process, showing readers how to manage each step in taking a film, TV, or media project from production to final delivery, from scheduling and budgeting through editing, sound, visual effects, and more. Accessibly written for producers, post supervisors, filmmakers, and students and extensively updated to address current digital and file-based industry practices, The Guide to Managing Postproduction for Film, TV, and Digital Distribution helps the reader to understand the new worlds of accessibility, deliverables, license requirements, legal considerations, and acquisitions involved in postproduction, including the ins and outs of piracy management and archiving. This edition addresses the standards for theatrical and digital distribution, network, cable and pay TV, as well as spotlights internet streaming and various delivery methods for specialty screenings, projection large format (PLF), and formats including 3D, virtual reality and augmented reality"--